Reciprocal Crossovers and a Positional Preference for Strand Exchange in Recombination Events Resulting in Deletion or Duplication of Chromosome 17p11.2 - Bi, Weimin (The American Society of Human Genetics, 2003)
Smith-Magenis syndrome (SMS) is caused by an ∼4-Mb heterozygous interstitial deletion on chromosome 17p11.2 in ∼80%–90% of affected patients. Three large (∼200 kb), complex, and highly homologous (∼98%) low-copy repeats (LCRs) are located inside or flanking the SMS common deletion. These repeats, also known as “SMS-REPs,” are termed “distal,” “middle,” and “proximal.” The directly oriented distal and proximal copies act as substrates for nonallelic homologous recombination resulting in both the deletion associated with SMS and the reciprocal duplication: dup(17)(p11.2p11.2). Using restriction enzyme cis-morphism analyses and direct sequencing, we mapped the regions of strand exchange in 16 somatic-cell hybrids that harbor only the recombinant SMS-REP. Our studies showed that the sites of crossovers were distributed throughout the region of homology between the distal and proximal SMS-REPs. However, despite ∼170 kb of high homology, 50% of the recombinant junctions occurred in a 12.0-kb region within the KER gene clusters. DNA sequencing of this hotspot (positional preference for strand exchange) in seven recombinant SMS-REPs narrowed the crossovers to an ∼8-kb interval. Four of them occurred in a 1,655-bp region rich in polymorphic nucleotides that could potentially reflect frequent gene conversion. For further evaluation of the strand exchange frequency in patients with SMS, novel junction fragments from the recombinant SMS-REPs were identified. As predicted by the reciprocal-recombination model, junction fragments were also identified from this hotspot region in patients with dup(17)(p11.2p11.2), documenting reciprocity of the positional preference for strand exchange. Several potential cis-acting recombination-promoting sequences were identified within the hotspot. It is interesting that we found 2.1-kb AT-rich inverted repeats flanking the proximal and middle KER gene clusters but not the distal one. The role of any or all of these in stimulating double-strand breaks around this positional recombination hotspot remains to be explored.